Three Centuries of Travel Writing by Muslim Women - Lambert-Hurley, Siobhan (Indiana University Press, 2022)
-- Lambert-Hurley is based in Sheffield, UK; Majchrowicz is based in Evanston, IL; and Sharma is based in Boston, MA -- This collection arose from a collaborative and multi-year research project which earned funding from the Leverhulme Trust. Entitled "Veiled Voyagers: Muslim Women Travellers from Asia and the Middle East" the project recovered, translated, annotated, and analyzed original texts gathered here and available in part on a website. -- The historical experiences of Muslim women offer a fascinating and understudied point of insight into the role of imperial, colonial, and global history. This collection not only recovers the voices of women from a broad range of languages but also provides the historical and cultural contexts necessary to understand the full import of what these women were trying to convey of their experiences in the world. -- Indiana University Press has a strong tradition of making space for the voices, perspectives, and experiences of Muslim women. This collection makes an important contribution to this tradition in its topic but perhaps more importantly it also encourages future scholarship in the field through the academic infrastructure which undergirds the texts included. -- The audience for the work is students and scholars of gender, Muslim identity, globalization, autobiographical and travel writing, women's studies, women's writing, colonial history, and religious history. -- The collection has an accompanying website (which is broader in scope to include both travel and autobiographical writing by Muslim women) at accessingmuslimlives.org.